2002
DOI: 10.1038/sj.jhh.1001461
|View full text |Cite
|
Sign up to set email alerts
|

Pulse pressure and coronary mortality in elderly men and women from general population

Abstract: The aim of this work was to evaluate whether pulse pressure (PP) in elderly people is a better predictor of coronary mortality than systolic and diastolic blood pressure taken alone. For this aim, 3282 elderly subjects aged у65 years were studied in a population-based frame. Blood pressure was repeatedly measured and averaged; historical data, anthropometrics, blood tests and 14-year coronary mortality were recorded. Statistics included analysis of covariance, Cox analysis and bivariate vectorial analysis. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 35 publications
1
53
1
2
Order By: Relevance
“…The increase of pulse pressure (the pulsatile component of blood pressure) is an age-related phenomenon and the common belief is that it is an indicator of large artery stiffness [18] and an established marker of cardiovascular risk in different clinical settings [19,20]. High pulse pressure may derive both from a rise in systolic values and from a decrease in diastolic values.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of pulse pressure (the pulsatile component of blood pressure) is an age-related phenomenon and the common belief is that it is an indicator of large artery stiffness [18] and an established marker of cardiovascular risk in different clinical settings [19,20]. High pulse pressure may derive both from a rise in systolic values and from a decrease in diastolic values.…”
Section: Discussionmentioning
confidence: 99%
“…This finding highlights the importance of using pulse pressure at an early stage of hypertension as a risk stratification tool, because pulse pressure-as opposed to SBP and DBP alone-has been shown to be a better predictor for adverse outcomes, especially in women. 18 Data from previous large hypertension trials have shown that most patients need combination therapy Figure 6 Blood pressure (BP) control rates for guideline-recommended dual therapies (percentage with 95% CI, adjusted for age, diabetes and ethnicity; for abbreviations see Figure 5a; # Po0.05 for gender differences). to achieve sufficient BP control.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] However, several studies have shown that awareness of hypertension and BP control is still suboptimal, 1 and thus effective strategies should be developed to improve BP control and adherence to therapy. One of the methods used to achieve these goals is represented by self-measurement of BP at home by automatic devices.…”
mentioning
confidence: 99%